Akt3 links mitochondrial function to the regulation of Aurora B and mitotic fidelity - Zachary J. Hough; Fatemeh Nasehi; Daniel G. Corum; Russell A. Norris; Ann C. Foley; Robin C. Muise-Helmericks (PLoS ONE, 2025)
Akt3 is a key regulator of mitochondrial homeostasis in the endothelium. Akt3 depletion results in mitochondrial dysfunction, decreased mitochondrial biogenesis, and decreased angiogenesis. Here we link mitochondrial homeostasis with mitotic fidelity—depletion of Akt3 results in the missegregation of chromosomes as visualized by multinucleation and micronuclei formation. We have connected Akt3 to Aurora B, a significant player in chromosome segregation. Akt3 localizes to the nucleus, where it associates with and regulates WDR12. During mitosis, WDR12 is localized to the dividing chromosomes, and its depletion results in a similar mitotic phenotype to Akt3 depletion. WDR12 associates with Aurora B, both of which are downregulated under conditions of Akt3 depletion. We used the model oxidant paraquat to induce mitochondrial dysfunction to test whether the Akt3-dependent effect on mitochondrial homeostasis is linked to mitotic function. Paraquat treatment also causes chromosome missegregation by inhibiting the expression of Akt3, WDR12, and Aurora B. The inhibition of ROS rescued both the mitotic fidelity and the expression of Akt3 and Aurora B. Akt3 directly phosphorylates the major nuclear export protein CRM-1, causing an increase in its expression, resulting in the inhibition of PGC-1 nuclear localization, the master regulator of mitochondrial biogenesis. The Akt3/Aurora B pathway is also dependent on CRM-1. CRM-1 overexpression resulted in chromosome missegregation and downregulation of Aurora B similar to that of Akt3 depletion. Akt3 null hearts at midgestation (E14.5), a stage in which proliferation is occurring, have decreased Aurora B expression, increased CRM-1 expression, decreased proliferation, and increased apoptosis. Akt3 null hearts are smaller and have a thinner compact cell layer than age-matched wild-type mice. Akt3 null tissue has dysmorphic nuclear structures, suggesting mitotic catastrophe. Our findings show that mitochondrial dysfunction induced by paraquat or Akt3 depletion results in a CRM-1-dependent disruption of Aurora B and mitotic fidelity.